(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Introduction: Nuclear medicine imaging techniques, specifically the DTPA (diethylenetriamine pentaacetate) renogram, play a vital role in diagnosis and management in pediatric nephrology. Due to the availability of prenatal ultrasonography, prenatal diagnosis of fetal renal disorders is increasing in frequency. Consequently, the number of patients undergoing DTPA renograms is increasing gradually. Objectives: This study was done to evaluate the role of DTPA renograms in the assessment of renal function in the pediatric age group and investigate the pattern of renogram findings in the under-5-year-old pediatric age group. Patients and Methods: This retrospective study was done on 138 patients below 5 years age consisting of 102 boys and 36 girls. They were referred to Institute of Nuclear Medicine & Allied Sciences (INMAS), Rajshahi for DTPA renogram from January 2023 to June 2023. To ensure proper image acquisition all the patients were administered ketamine with prior preparations. Average administered dose of 99mTc-pertechnetate-labeled DTPA in boys was 2.51 mCi, and in girls it was 2.36 mCi. Images were acquired with a Siemens (Symbia Intevo Bold) dual-headed gamma camera. The total time required for image acquisition was about 30 minutes for each patient. After image acquisition, ROI was drawn, and the calculation of GFR, split functions, and other parameters were calculated. Result: The study showed unilateral hydronephrosis in 59.42% of patients, bilateral hydronephrosis in 33.33% of patients, and no hydronephrosis in 7.24% of patients. 22.46% of patients were diagnosed prenatally by ultrasound. Total GFR was found to be reduced in 13.04% of patients, and split function was found to be reduced in 40.58% of patients. However, the majority (68.12%) of the patients showed no feature of nephropathy, 27.54% were diagnosed with unilateral nephropathy, and 4.35% had bilateral nephropathy. A minority (4.35%) of the patients had unilateral renal agenesis. Renogram findings were partially incompatible with ultrasound findings in 28 (20.29%) patients. Conclusion: DTPA renogram can play a very important role in assessing renal function in patients with renal pathologies for diagnosis and management. Despite several drawbacks, including radiation and a longer time for image acquisition, its use is increasing every day because of its affordability and feasibility. Bangladesh J. Nuclear Med. 26(2): 184-187, 2023